Abdominal Aortic Calcification Is Associated with Decline in Handgrip Strength in the U.S. Adult Population ≥40 Years of Age - Garcia-Hermoso, A (Elsevier B.V., 2021)
Background and aims: The present study investigated the association between abdominal aortic calcification (AAC) and handgrip strength (HGS) and the ability of HGS to predict an increased AAC phenotype in adults. Methods and results: The analysis consisted of data for 3140 men and women aged ≥40 years (51.7% women) from the 2013–2014 NHANES. Lateral scans of the thoraco-lumbar spine (L1–L4) were scored for AAC using a validated 8-point scale (AAC-8); subjects with a score of ≥3 were considered at increased risk for cardiovascular disease due to a high AAC phenotype. HGS was assessed using a grip dynamometer. The prevalence of severe AAC in the population was 9.0%. Decline in HGS was associated with higher AAC-8 scores in men and women (p < 0.001). General linear model analysis showed that HGS levels were negatively associated with high AAC (p < 0.001) and AAC-8 status for both sexes. Likewise, for each 5-kg higher HGS, there lower odds of a high AAC phenotype (in men OR = 0.73, CI95%, 0.64–0.84) and (women OR = 0.58, CI95%, 0.47–0.70). Receiver operating characteristic curve analysis showed that the HGS threshold value to detect high risk of AAC in adults was ≥37.3 kg (AUC = 0.692) in men and 25.1 kg (AUC = 0.705) in women. Conclusion: Lower muscular strength, as measured by HGS, is associated with higher AAC scores in the U.S. population ≥40 years of age. Accordingly, maintenance of muscular strength during aging may protect adults against vascular calcification, an independent predictor of cardiovascular events. HGS measurement seems to be a valid screening tool for detecting a high ACC phenotype in adults. © 2020 The Italian Diabetes Society, the Italian Society for the Study of Atherosclerosis, the Italian Society of Human Nutrition and the Department of Clinical Medicine and Surgery, Federico II University